Career guidance and counselling in schools - Bócsa, Eva (НТУ "ХПІ", 2013)
The hereby paper, after defining fundamental notions (career, profession, occupation, vocation, etc.) and briefly displaying certain theories regarding career guidance and counselling, analyzes the main activities carried out by counsellors: providing support with a view of self-knowledge and personal development, exploring educational and professional routes, personal ad.

У даній статті ми визначили основні терміни, а також представили деякі теорії з приводу орієнтації і консультування в кар'єрі. Потім ми проаналізували основні профорієнтаційні заходи: надання допомоги в самопізнанні та особистісному зростанні, вивчення освітніх і професійних шляхів, особистісне просування.
Орієнтування та консультування з побудови кар'єри в школах
Keywords: кар'єра; діяльність професійна; покликання